2006
DOI: 10.1007/s00737-006-0148-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal bond and mother–child interaction in severe postpartum psychiatric disorders: Is there a link?

Abstract: Mothers in the puerperium are vulnerable to a wide spectrum of postpartum psychiatric disorders. One of the central psychological processes of the puerperium is the development of an emotional relationship with the baby. The bond to the infant as well as the interaction with the baby are two aspects of the mother-infant relationship that can be disturbed by mothers with postpartum psychiatric disorders. Dysfunctional maternal cognitions may also influence the development of an emotional bonding and the establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 14 publications
3
58
0
8
Order By: Relevance
“…They also found that depressed women reported more negative evaluations of themselves as parents than did non-depressed women, even if no difference was found in observed maternal interactive behavior. Similarly, Hornstein et al [30] found Table 2. Comparisons between mothers with and without depressive symptoms and sex of infant according to parental bonding (N = 100) (Mean, SD).…”
Section: Discussionmentioning
confidence: 74%
“…They also found that depressed women reported more negative evaluations of themselves as parents than did non-depressed women, even if no difference was found in observed maternal interactive behavior. Similarly, Hornstein et al [30] found Table 2. Comparisons between mothers with and without depressive symptoms and sex of infant according to parental bonding (N = 100) (Mean, SD).…”
Section: Discussionmentioning
confidence: 74%
“…Ressalvamos, como notam Brockington et al (2001), que este deve ser apenas um de vários instrumentos a utilizar na avaliação da ligação mãe/pai-bebé, que beneficia particularmente da adoção de metodologias observacionais. A este respeito, importa referir que os resultados do PBQ se têm revelado consistentes com os dados da observação clínica (Hornstein, Trautmann-Villalba, Rave, Wortmann-Fleischer, & Schwarz, 2006). Klier (2006) sugere ainda que, em contexto clínico, o PBQ seja utilizado como medida de avaliação da evolução dos utentes ao longo do processo terapêutico.…”
Section: Discussionunclassified
“…There is a body of feminist literature which argues that postpartum distress is a natural reaction to the change and loss which follows childbirth (Littlewood & McHugh, 1997;Nicholson, 1999;Oakley, 1980). The link between postpartum mental illness and an increased chance of attachment difficulties has been documented (Gerhardt, 2004;Hannah, 2005;Hornstein, Trautmann-Villalba, Hohm, Rave, Wortmann-Fleischer & Schwarz, 2006;Milgrom, Martin & Negri, 2003;Parsons, 2009). If a mother experiences postpartum distress it is likely to impinge upon, and interfere with, her ability to bond with her baby.…”
Section: Introductionmentioning
confidence: 99%